Cardiac Electrophysiologic Effects of Different Local Anesthetics in Langendorff-Perfused Rabbit Hearts - Julian Wolfes; Amy Katthöfer; Felix Wegner; Benjamin Rath; Florian Doldi; Sati Güler-Eren; Lars Eckardt; Gerrit Frommeyer; Christian Ellermann (Cardiovascular Toxicology, 2026)

Electrophysiological Profile of Different Antiviral Therapies in a Rabbit Whole-Heart Model - Julian Wolfes; Lina Kirchner; Florian Doldi; Felix Wegner; Benjamin Rath; Lars Eckardt; Christian Ellermann; Gerrit Frommeyer (Cardiovascular Toxicology, 2024)
Antiviral therapies for treatment of COVID-19 may be associated with significant proarrhythmic potential. In the present study, the potential cardiotoxic side effects of these therapies were evaluated using a Langendorff model of the isolated rabbit heart. 51 hearts of female rabbits were retrogradely perfused, employing a Langendorff-setup. Eight catheters were placed endo- and epicardially to perform an electrophysiology study, thus obtaining cycle length-dependent action potential duration at 90% of repolarization (APD 90 ), QT intervals and dispersion of repolarization. After generating baseline data, the hearts were assigned to four groups: In group 1 (HXC), hearts were treated with 1 µM hydroxychloroquine. Thereafter, 3 µM hydroxychloroquine were infused additionally. Group 2 (HXC + AZI) was perfused with 3 µM hydroxychloroquine followed by 150 µM azithromycin. In group 3 (LOP) the hearts were perfused with 3 µM lopinavir followed by 5 µM and 10 µM lopinavir. Group 4 (REM) was perfused with 1 µM remdesivir followed by 5 µM and 10 µM remdesivir. Hydroxychloroquine- and azithromycin-based therapies have a significant proarrhythmic potential mediated by action potential prolongation and an increase in dispersion. Lopinavir and remdesivir showed overall significantly less pronounced changes in electrophysiology. In accordance with the reported bradycardic events under remdesivir, it significantly reduced the rate of the ventricular escape rhythm.

Divergent Electrophysiological Effects of Loperamide and Naloxone in a Sensitive Whole-Heart Model - Julian Wolfes; Christian Ellermann; Sophie Burde; Patrick Leitz; Nils Bögeholz; Kevin Willy; Michael Fehr; Florian Reinke; Lars Eckardt; Gerrit Frommeyer (Cardiovascular Toxicology, 2021)

Concomitant Treatment with Proton Pump Inhibitors and Cephalosporins Does Not Enhance QT-Associated Proarrhythmia in Isolated Rabbit Hearts - Julian Wolfes; Christian Ellermann; Sophie Burde; Patrick Leitz; Nils Bögeholz; Kevin Willy; Michael Fehr; Lars Eckardt; Gerrit Frommeyer (Cardiovascular Toxicology, 2020)

Proarrhythmic Effect of Acetylcholine-Esterase Inhibitors Used in the Treatment of Alzheimer’s Disease: Benefit of Rivastigmine in an Experimental Whole-Heart Model - Christian Ellermann; Alix Coenen; Philipp Niehues; Patrick Leitz; Simon Kochhäuser; Dirk G. Dechering; Michael Fehr; Lars Eckardt; Gerrit Frommeyer (Cardiovascular Toxicology, 2020)

Action Potential Triangulation Explains Acute Proarrhythmic Effect of Aliskiren in a Whole-Heart Model of Atrial Fibrillation - Christian Ellermann; André Mittelstedt; Julian Wolfes; Kevin Willy; Patrick Leitz; Florian Reinke; Lars Eckardt; Gerrit Frommeyer (Cardiovascular Toxicology, 2020)

Digitalis Promotes Ventricular Arrhythmias in Flecainide- and Ranolazine-Pretreated Hearts - Christian Ellermann; Julian Wolfes; Dirk Puckhaber; Nils Bögeholz; Patrick Leitz; Philipp S. Lange; Lars Eckardt; Gerrit Frommeyer (Cardiovascular Toxicology, 2019)

Ivabradine Aggravates the Proarrhythmic Risk in Experimental Models of Long QT Syndrome - Gerrit Frommeyer; Jan Weller; Christian Ellermann; Patrick Leitz; Simon Kochhäuser; Philipp S. Lange; Dirk G. Dechering; Lars Eckardt (Cardiovascular Toxicology, 2019)

Additive Proarrhythmic Effect of Combined Treatment with QT-Prolonging Agents - Gerrit Frommeyer; Christina Fischer; Christian Ellermann; Dirk G. Dechering; Simon Kochhäuser; Philipp S. Lange; Kristina Wasmer; Michael Fehr; Lars Eckardt (Cardiovascular Toxicology, 2018)

The anti-influenza drug oseltamivir reduces atrial fibrillation in an experimental whole-heart model - Gerrit Frommeyer; André Mittelstedt; Julian Wolfes; Christian Ellermann; Simon Kochhäuser; Patrick Leitz; Dirk G. Dechering; Lars Eckardt (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Severe Proarrhythmic Potential of the Antiemetic Agents Ondansetron and Domperidone - Gerrit Frommeyer; Christina Fischer; Christian Ellermann; Philipp S. Lange; Dirk G. Dechering; Simon Kochhäuser; Michael Fehr; Lars Eckardt (Cardiovascular Toxicology, 2017)

Severe proarrhythmic potential of risperidone compared to quetiapine in an experimental whole-heart model of proarrhythmia - Gerrit Frommeyer; Henning von der Ahe; Benedict Brücher; Dirk G. Dechering; Philipp S. Lange; Florian Reinke; Kristina Wasmer; Julia Köbe; Christian Pott; Gerold Mönnig; Lars Eckardt (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)